Mapping ecosystems through Design: reflections of the DesignOBS project - Costa, Nina (2022)
This chapter explores the results obtained from the application of a participatory process used to interpret databases about the Design discipline. This project was undertaken within the project: For a Design Observatory in Portugal (DesignOBS). The challenge focused on developing a one-page visualisation about at least one database focused on a vector of the design ecosystem (design companies, design research, design education). In total, 41 works from 70 design students from two different schools and 9 works from design professionals, with multiple backgrounds, were collected. After a preliminary selection, the results were displayed in the first exhibition of the DesignOBS project at the Faculty of Fine Arts, University of Lisbon. This chapter presents into the results obtained - it provides a description of the visual projects and reflects on the potential contributions of using design as an approach to support the mapping of ecosystems in Portugal and abroad.